Vestimentary eponyms in contemporary Spanish language - Y. V. Slivchikova (MGIMO University Press, 2014)
In a consequence of the perpetual changes in the world of fashion, which can be explained by the introduction of new tendencies, materials and designers, the vocabulary that describes clothing enlarges by the internal means of the language and with the help of lexical borrowing. The article considers the characteristic usage of terms-eponyms for clothing description in Spanish language. Eponyms complicate the learning of languages and translation being a result of the worldview reflection of a determinate group of people in a determined period of time. As the study sets out to find out and explain the connotative meanings of vestimentary eponyms and suggest an approach for synonyms choice from their family for the discourse purposes, the toponyms are not taken into consideration, and the study concentrates on the anthroponyms, proper nouns which identify people, because they can adjust special connotative meanings to the terms within cultural linguistics context. The author shows the examples of etymology of originally Spanish and borrowed terms. Their comparison allows to make out the principles for the classification, authenticity and internationality amongst them. This classification divides all the vestimentary terms-eponyms into two main groups (neutral and with connotative meaning). Then it is possible to systematize and explain the meaning of the second group. According to the study international borrowed terms-eponyms look to neutrality, but among other synonyms acquire the meaning of elitism. Not international vestimentary terms-eponyms have a special connotative meaning, which is known amongst native speakers, that is why while teaching or translating more attention should be paid to them.